Pelatihan Penulisan Karya Ilmiah Pada Guru-guru SMA Negeri 6 Padangsidimpuan Dalam Pengembangan Kompetensi Profesionalisme Guru - Eni Sumanti Nasution; Fauziah Nasution; Tinur Rahmawati Harahap; Elissa Evawani Tambunan; Ali Padang Siregar (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service is carried out in which the activities obtained find a problem at SMA Negeri 6 Padangsidimpuan. The problems found in increasing the professional development of teachers where one of the activities is through academic development and the development of teacher functional positions. In this case one of the conditions in this increase is to make a scientific work. In this case the teacher experiences difficulties in writing scientific papers starting from the introduction in making a background problem, methods and discussions that are in accordance with the research conducted by the teacher. With this activity, teachers can be trained in writing good scientific work. This activity was carried out at SMA Negeri 6 Padangsidimpuan which was attended by 30 teachers. The method used is to use training through a quantitative approach to the results. This dedication activity has stages starting from planning, implementing and analyzing training in writing scientific papers for teachers of SMA Negeri 6 Padangsidimpuan. The result of this community service activity is that teachers understand better how to write scientific papers and are already able to make scientific work in accordance with the research being conducted.